Husband's international migration: Decision-making autonomy among left-behind wives in rural area of central Myanmar. Issue 1 (24th October 2019) - Shwe, Win Win; Jampaklay, Aree; Chamratrithirong, Aphichat; Thaweesit, Suchada
Abstract : Purpose: The purpose of this paper is to understand the effects of the husband's migration on wives' decision-making autonomy. Design/methodology/approach: The study setting is Magway Region of central Myanmar where poverty has driven adult males to migrate overseas. The study hypothesizes that the absence of husbands due to international migration leads to changes in the roles and decision-making power of left-behind wives. A cross-sectional survey was conducted in 22 villages of Pakkoku district, Magway Region, using the multi-stage random sampling method. The study sample included 205 migrant's wives and 196 non-migrant's wives. Findings: The international migration of husbands has a strong and positive impact on left-behind wives' autonomy independent of individual characteristics and household social and economic status. In addition, the findings show that the number of children and household wealth are positively associated with women's autonomy, whereas household size shows a negative association. Research limitations/implications: It is possible that there will be unmeasured selection factors such as unsuccessful migration as it might influence both husbands' migration status and women's autonomy. Cross-sectional data also invite a question about the causal relationship. For example, it might be possible that women with high autonomy may be more likely to encourage their husband to work abroad. So, the relationship might be the other way around. A further longitudinal study is also needed to describe detail explanation about the causal influence of left-behind women's autonomy. Originality/value: Successful international migration has a impact not only on women's autonomy but also on household economic status in central rural Myanmar.